Assessment of a rapid pan-antibody dot test for detection of antibodies against SARS-CoV-2 - Haq, Md Ahsanul; Jamiruddin, Maha; Khondoker, Mohib Ullah; Ahmed, Md Firoz; Khandker, Shahad Saif; Ali, Tamanna; Mostafi, Mamun; Sil, Bijon Kumar; Adnan, Nihad; Jamiruddin, Mohd Raeed (Bangladesh Journal of Medical Science, 2021)
Background: With the drastic spread of COVID-19 and mass mortality of people globally, detection of the progression of this disease has stood out to be a necessity. Hence, we set out to identify the prevalence of COVID-19 antibodies in Bangladesh using the in-house rapid pan-immunoglobulin dot-blot test kit and evaluate the performance of this kit. Methods: In this cross-sectional study, we tested serum collected between mid-May and mid-June 2020 for COVID-19 antibodies by using the in-house rapid pan-immunoglobulin dot-blot test kit in RTPCR confirmed patients with symptoms for 1-7 days (Group Ia; n =100) and 8-14 days (Group Ib; n = 100); symptomatic RT-PCR negative patients (Group II; n = 100) and convalescent patients (Group III; n = 109) while comparing with pre-pandemic sera samples collected prior two years to December-2019 (Group IV; n = 100). Results: Our kit detected that almost 70% of the convalescent patients produced antibodies against COVID-19 compared to other groups. However, the group with individuals at the end phase of COVID-19 exhibited the second-highest percentage of seroprevalence (41%). We also observed that though Group II was RT-PCR negative, 20% of them showed COVID-19 antibodies. Conclusion: With a specificity of 96% in our kit, we can say that our kit will be a potential device for the detection of SARS-CoV-2 antibodies and to understand herd immunity in Bangladesh. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.131-139